Developing Students' Knowledge of English Through a Creative Approach (Texas Journal of Philology, Culture and History, 2022)
The aim of this article was to reveal the students’ attitude towards the integration of creativity development when studying foreign languages at public schools. To investigate the students’ attitude towards the development of creativity during foreign language classes, importance of environment and teachers’ assistance.